2011
DOI: 10.1111/j.1365-2966.2011.20150.x
|View full text |Cite
|
Sign up to set email alerts
|

Steep faint-end slopes of galaxy mass and luminosity functions at z≥ 6 and the implications for reionization

Abstract: We present the results of a numerical study comparing photometric and physical properties of simulated z= 6–9 galaxies to the observations taken by the Wide Field Camera 3 instrument aboard the Hubble Space Telescope. Using cosmological hydrodynamical simulations we find good agreement with observations in colour–colour space at all studied redshifts. We also find good agreement between observations and our Schechter luminosity function fit in the observable range, Muv≤−18, provided that a moderate dust extinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
136
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(163 citation statements)
references
References 64 publications
(170 reference statements)
26
136
1
Order By: Relevance
“…The steep rise of the SFR function in the presence of radiative heating and SNe at low SFRs down to the SFRs that our simulations do not accurately resolve is consistent with that seen in previous works (e.g., Finlator, Davé,Özel 2011;Jaacks et al 2012;Cai et al 2014), and with extrapolations of the observed SFR function (e.g., Smit et al 2012;Bouwens et al 2014a;Finkelstein et al 2014;Duncan et al 2014). Because the mass scale below which photoheating affects the SFRs of galaxies is close to the mass scale below which efficient gas cooling requires the presence of molecular hydrogen or metals, quantifying the precise impact of reionization on the UV luminosity function will require more detailed, higher-resolution simulations of galaxy formation that include the relevant gas physics.…”
Section: The Uv Luminosity Function As a Probe Of Reionizationsupporting
confidence: 91%
“…The steep rise of the SFR function in the presence of radiative heating and SNe at low SFRs down to the SFRs that our simulations do not accurately resolve is consistent with that seen in previous works (e.g., Finlator, Davé,Özel 2011;Jaacks et al 2012;Cai et al 2014), and with extrapolations of the observed SFR function (e.g., Smit et al 2012;Bouwens et al 2014a;Finkelstein et al 2014;Duncan et al 2014). Because the mass scale below which photoheating affects the SFRs of galaxies is close to the mass scale below which efficient gas cooling requires the presence of molecular hydrogen or metals, quantifying the precise impact of reionization on the UV luminosity function will require more detailed, higher-resolution simulations of galaxy formation that include the relevant gas physics.…”
Section: The Uv Luminosity Function As a Probe Of Reionizationsupporting
confidence: 91%
“…For instance, our LF results at z ∼ 7 are in good agreement with the hydrodynamical simulations of Jaacks et al (2012) with M å = −20.82 and log(f å ) = −3.74, although they predict a steeper faint-end slope of α = −2.30 down to a similar lower magnitude limit of M UV = −15. Theoretical models by Mason et al (2015) find a closer slope of α = −1.95 ± 0.17 down to a magnitude limit of M UV = −12, corresponding to a halo mass of 10 9 M e .…”
Section: The Uv Lf At Z = 6-7supporting
confidence: 85%
“…For comparison, the faint-end slope at z < 0.5 is very shallow (α ∼ −1.3), which indicates a decreasing contribution of faint star-forming galaxies to the total star formation density toward lower redshift Schiminovich et al 2005). The predicted evolution of the dark matter halo mass function based on cosmological simulations predicts an even steeper slope of α ∼ 2.3 of the UV LF at high redshift (Jaacks et al 2012). The deepest HST observations of blank fields, such as the XDF, put constraints on the faint-end slope down to an absolute magnitude of M 17.5 AB UV~-.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The latter prediction is supported by observations that the two strongest C IV absorbers at z ∼ 6 are physically associated with Lyman-α emitters (Díaz et al 2014), whose stellar mass is characteristically 10 8 -10 10 M⊙ (Lidman et al 2012). The tendency for low-ionization metal absorbers to trace predominantly lower-mass galaxies (Becker et al 2011;Finlator et al 2013;Kulkarni et al 2013) immediately promotes them to a critical constraint on the origin of the UVB and of cosmological reionization because current models for reionization tend to rely heavily on low-mass galaxies to provide the required flux of ionizing photons (Finlator et al 2011;Alvarez et al 2012;Kuhlen & Faucher-Giguère 2012;Jaacks et al 2012;Robertson et al 2013;Duffy et al 2014;Wise et al 2014). Such systems are generally too faint to be observed in emission, hence low-ionization absorbers will remain the only way to constrain their abundance for the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%